Prevalence of sickle cell disease in tribal peoples of Valsad district region in Gujarat,India - Dr. Sunita Mistry; Dr. Kamlesh Shah; Dr. Jignasha Patel (Tropical Journal of Pathology and Microbiology, 2018)
Background: High prevalence of sickle gene has been demonstrated in various tribal communities of Gujarat including Bhils and Dhodias of Panchmahal, Dublas, Naikas, Koli, Dhanka, Gamit, Vasava, Bariya, Varli, Vaghari, Kukna, Halpati, Chaudhari etc. The present study was conducted with an objective to document the prevalence of sickle cell diseasein Valsad district of Gujarat state. Methodology: The study is conducted as a retrospective survey in GMERS Medical College and hospital, Valsad between January 2015 to December 2016 were screened for sickle cell anemia by sickling test (with freshly prepared sodium metabisulphite). Those found positive for sickling test, were further analyzed by HPLC (high-performance liquid chromatography) to confirm their status as either sickle cell trait or sickle cell disease. Results: Out of 1186 cases number of male cases were 277 (23.35%) and females were 909 (76.64%) cases. The gender distribution of male to female cases is 1:3. 88.7% cases were sickle cell trait, 9.02% cases were sickle cell disease, 1.68% cases were sickle beta thalassemia, 0.25% cases were B Thalassemia Minor and 0.33% cases were B Thalassemia Major. In the present study, among the 1186 cases, 397(33.47%) were from Patel (Dhodia) community, 97 (8.17%) were from varli community, 57(4.8%) were from Halpati community and 51(4.3%) were from Dhodi community followed by other backward community. Conclusion: It was concluded that Dhodias, Varli, Halpati and Dhodi were the most common community of sickle cell disorders in tribal peoples of Valsad district.Among the Sickling test positive cases, Sickle cell trait and sickle cell disease was the most common variant.